Edukasi Kesehatan Masyarakat Melalui Disinfaksi dan Penggunaan Masker Sebagai Upaya Pencegahan Penyebaran Virus Covid-19 di Panti Asuhan Al-Isti’anah Kediri Kabupaten Lombok Barat - Indrawati, Indrawati; Santosa, Farah Heniati; Bahri, Samsul; Samsuriadi, Samsuriadi (Jurnal Pengabdian UNDIKMA, 2021)
The purpose of implementing this service activity is to make efforts to break the Covid-19 chain by distributing disinfectants, disinfectants and masks for administrators and foster children of the Al-Isti’anah Orphanage Kediri, West Lombok. The method of implementing this service is by providing disinfection tools, disinfectant fluids, and masks to the administrators of the Al-Isti’anah Orphanage Kediri, West Lombok. The results of this service activity were providing disinfection kits, disinfectant fluids and masks to the Al-Isti’anah Orphanage, Kediri, West Lombok. In addition, the community service team provided education about the importance of disinfection in the orphanage area to reduce the possible risk of spreading and spreading the covid-19 virus to the caretakers and children of the residents of the Al-Isti’anah orphanage, Kediri, West Lombok. By carrying out health education through disinfection and the use of masks, the administrators of the Al-Isti’anah Orphanage better understand the importance of disinfection in the orphanage area and the obedience of caregivers and children in using masks when interacting in the orphanage environment.